Phenotypic spectrum of the SMAD3-related aneurysms–osteoarthritis syndrome. Issue 1 (13th December 2011) - van de Laar, Ingrid M B H; van der Linde, Denise; Oei, Edwin H G; Bos, Pieter K; Bessems, Johannes H; Bierma-Zeinstra, Sita M; van Meer, Belle L; Pals, Gerard; Oldenburg, Rogier A; Bekkers, Jos A; Moelker, Adriaan; de Graaf, Bianca M; et al.
Abstract : Background: Aneurysms–osteoarthritis syndrome (AOS) is a new autosomal dominant syndromic form of thoracic aortic aneurysms and dissections characterised by the presence of arterial aneurysms and tortuosity, mild craniofacial, skeletal and cutaneous anomalies, and early-onset osteoarthritis. AOS is caused by mutations in the SMAD3 gene. Methods: A cohort of 393 patients with aneurysms without mutation in FBN1, TGFBR1 and TGFBR2 was screened for mutations in SMAD3 . The patients originated from The Netherlands, Belgium, Switzerland and USA. The clinical phenotype in a total of 45 patients from eight different AOS families with eight different SMAD3 mutations is described. In all patients with a SMAD3 mutation, clinical records were reviewed and extensive genetic, cardiovascular and orthopaedic examinations were performed. Results: Five novel SMAD3 mutations (one nonsense, two missense and two frame-shift mutations) were identified in five new AOS families. A follow-up description of the three families with a SMAD3 mutation previously described by the authors was included. In the majority of patients, early-onset joint abnormalities, including osteoarthritis and osteochondritis dissecans, were the initial symptom for which medical advice was sought. Cardiovascular abnormalities were present in almost 90% of patients, and involved mainly aortic aneurysms and dissections. Aneurysms and tortuosity were found in the aorta and other arteries throughout the body, including intracranial arteries. Of the patients who first presented with joint abnormalities, 20% died suddenly from aortic dissection. The presence of mild craniofacial abnormalities including hypertelorism and abnormal uvula may aid the recognition of this syndrome. Conclusion: The authors provide further insight into the phenotype of AOS with SMAD3 mutations, and present recommendations for a clinical work-up.